APPLICATION OF FIVE-STAGE CONCEPTUAL TEACHING MODEL BY UTILIZING CMAPTOOLS TO ANALYZE CONCEPTUAL CHANGE AND COGNITIVE LEARNING OUTCOMES ON LIGHT AND OPTICS TOPIC - Rofiuddin, Muhammad Rifqi (2014)
Science teachers need to help students identify their prior ideas and modify them based on scientific knowledge. This process is called as conceptual change. One of essential tools to analyze students' conceptual change is by using concept map. Concept Maps are graphical representations of knowledge that are comprised of concepts and the relationships between them. Constructing concept map is implemented by adapting the role of technological information and communication, as it is suitable with Educational Ministry Regulation No.68 year 2013 that stated the aids of multimedia to support learning process. Institute for Human and Machine Cognition (IHMC) has developed CmapTools, a client-server software for easily construct and visualize concept maps. This research aims to investigate secondary students' conceptual change and cognitive learning outcomes after experiencing five-stage conceptual teaching model by utilizing CmapTools in learning Light and Optics. Convergent parallel mixed method is implemented in order to collect and assess conceptual change as qualitative data and cognitive learning outcomes as quantitative data. Sample was taken purposively (n= 22 students) at grade VIII in an International School Bandung, West Java. Conceptual change based on comparison of preliminary and post concept map construction is assessed based on rubric of concept map scoring and structure whereas cognitive learning outcomes is assessed based on normality gain in each cognitive level from C1 (remembering) until C4 (analyzing) aspect. Results shows significance conceptual change differences at 50.92 % that is elaborated into concept map element based on Novak and Gowin's criteria such as prepositions and hierarchical level in high category, cross links in medium category and specific examples in low category. Strong correlation coefficient (rxy = 0.78) illustrates the implementation of five-stage conceptual teaching model by utilizing CmapTools in helping students to construct concept map is capable to improve secondary students' cognitive learning outcomes in high category that is obtained based on normalized gain value <g = 0.86>. All of the results are supported with the students' positive response towards CmapTools utilization that indicates improvement of motivation, interest, and behavior aspect towards Physics lesson. ABSTRAK Tenaga pendidik sains diperlukan untuk membantu dalam mengidentifikasi dan memodifikasi konsepsi awal siswa berdasarkan pengetahuan ilmiah melalui proses perubahan konseptual. Peta konsep adalah salah satu alat untuk menganalisis perubahan konseptual sebagai representasi grafis yang tersusun atas hubungan antar konsep. Membangun peta konsep dapat diimplementasikan dengan mengadaptasi peran teknologi dan komunikasi, sebagaimana tertuang dalam Peraturan Menteri Pendidikan No. 68 tahun 2013 yang menyatakan penggunaan multimedia dalam proses pembelajaran. Institute for Human and Machine Cognition (IHMC) telah mengembangkan CmapTools, sebuah software berbasis klien server yang memberikan kemudahan dalam memvisualisasi konsep. Penelitian ini bertujuan untuk menginvestigasi perubahan konseptual dan hasil belajar kognitif siswa melalaui implementasi model pembelajaran konseptual lima tahap dengan menerapkan CmapTools pada topik Cahaya dan Optik. Implementasi Mixed method berbasis konvergen parallel dimaksudkan untuk mengumpulkan dan mengevaluasi secara bersama perubahan konseptual sebagai data kualitatif dan hasil belajar kognitif sebagai data kuantitatif. Sampel penilitian diambil secara purposif (n=22) pada kelas VIII di sebuah Sekolah Internasional, Bandung, Jawa Barat. Perubahan konseptual berdasarkan perbandingan konstruksi peta konsep sebelum dan sesudah dievaluasi melalui rubrik skoring dan struktur, sedangkan hasil belajar kognitif dari pretes dan posttes dievaluasi melalui gain ternormalisasi pada tiap tahapan kognitif dari C1 (mengingat) hingga C4 (menganalisis). Hasil menunjukkan perbedaan konseptual yang signifikan sebesar 50.92% yang dielaborasi berdasarkan kriteria peta konsep menurut Novak dan Gowin yaitu hubungan dan struktur hirarki pada kategori tinggi, hubungan silang pada katergori sedang, dan contoh pada kategori rendah. Besarnya nilai koefisien korelasi (rxy = 0.78) menunjukkan bahwa pembelajaran lima tahap perubahan konseptual dengan menerapkan CmapTools mampu untuk meningkatkan hasil belajar kognitif pada kategori tinggi <g=0.78). Hasil ini didukung oleh respon positif siswa terhadap penerapan CmapTools yang mengindikasi peningkatan motivasi, minat dan sikap siswa terhadap pembelajaran fisika.